Using Multidimensional Contingency Coefficient to Discrimination Arabic Poems for Sample of Poets - رحمة, عبد المنعم صالح; حمود, مها عبد الكريم (Journal of Economics and Administrative Sciences, 2025)
The purpose of this paper to discriminate between the poetic poems of each poet depending on the characteristics and attribute of the Arabic letters. Four categories used for the Arabic letters, letters frequency have been included in a multidimensional contingency table and each dimension has two or more levels, then contingency coefficient calculated.The paper sample consists of six poets from different historical ages, and each poet has five poems. The method was programmed using the MATLAB program, the efficiency of the proposed method is 53% for the whole sample, and between 90% and 95% for each poet's poems.